2012
DOI: 10.4193/rhino12.073
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between peak nasal inspiratory flow and peak expiratory flow in children and adolescents

Abstract: Background: PEAK nasal inspiratory flow (PNIF) has been proposed as a simple method to evaluate nasal patency. Asthma and allergic rhinitis are commonly associated, and lower airway assessment can provide information concerning an objective interpretation of nasal function. Aims: TO determine whether the PNIF is correlated with peak expiratory flow (PEF) in children and adolescents. Methods and results: Cross-sectional study carried out in healthy students randomly chosen in 14 public schools of the city of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Noninvasive and easy to use evaluation procedures have remained a constant challenge for clinical practice. Currently, PNIF has been used in upper airway assessment, 8 , 21 , 22 but in the reviewed literature, studies about nasal patency, related to rhinitis signs and symptoms as well as orofacial aspects in children, have not been found.…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive and easy to use evaluation procedures have remained a constant challenge for clinical practice. Currently, PNIF has been used in upper airway assessment, 8 , 21 , 22 but in the reviewed literature, studies about nasal patency, related to rhinitis signs and symptoms as well as orofacial aspects in children, have not been found.…”
Section: Discussionmentioning
confidence: 99%
“…This supports the fact that posterior arch width is a good support for the diagnosis of posterior crossbite The presence of AR was found to be marginally significant (not quite at the 5% level) meaning that AR has only a slight effect on the presence of posterior crossbite/ogival palate. Since some studies have demonstrated that upper and lower airway functions are strictly correlated [29,30] even in pediatric populations [31], the presence of asthma was also considered in order to evaluate its possible influence on malocclusion in children. In this study, differently from AR and previous experiences conducted on children/adolescents affected by lower airway obstruction [14,32], the percentage of subjects with asthma did not differ in the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…All relevant and general information, including sociodemographic variables, such as age, weight, height, income, education, and self-reported color, was registered. 13 …”
Section: Methodsmentioning
confidence: 99%
“…Exposure to intimate partner violence and lack of asthma control in adults: a cross-sectional study | ORIGINAL ARTICLE information, including sociodemographic variables, such as age, weight, height, income, education, and self-reported color, was registered. 13 The following questionnaires validated in Brazil were applied to all individuals at baseline:1) Beck Scale for Depression; 14 2) Waldnig and Young's scale of resilience; 15 3) Questionnaire to assess the level of psychological stress; 16 4) CTS2 was proposed and developed by Straus to identify different aspects of domestic violence with at least 1 year in a stable marital situation 17 and validated for Portuguese. 18 The CTS2 evaluated the variety of tactics used in response to the conflict with the partner but did not identify the causes of damage and health problems or the meaning of violent acts.…”
Section: Main Measures Variables and Outcomesmentioning
confidence: 99%